Analysing the Study of Organizational Justice Configuration and Social Modal on Satisfaction and Commitment - Heru Kurnianto Tjahjono; Yuliza Yuliza (Indonesian Journal of Multidisciplinary Science, 2022)
This study is a critical review of an article written by Heru Kurnianto Tjahjono, Olivia Fachrunnisa, and Majang Palupi and had published in the International Journal Business Excellence 2019, 17(3): 336-360 under the heading of “ Configuration of organizational justice and social capital: their impact on satisfaction and commitment”. The purpose of this study is to explain individual behavior in evaluating distributed justice and procedural justice. The method is done by reviewing a number of literature related to the topic of the article. The result indicates that contextual aspects, such as distributive justice, procedural justice, and social capital, play a large role in elaborating satisfaction and organizational commitment. Future studies are important to conduct a broader review of the impact on job satisfaction and organizational commitment in different contexts such as different industries, among different workers generations, and other demographic factors.